Multicentury Instability of the Atlantic Meridional Circulation in Rapid Warming Simulations With GISS ModelE2. Issue 12 (20th June 2018) - Rind, David; Schmidt, Gavin A.; Jonas, Jeff; Miller, Ron; Nazarenko, Larissa; Kelley, Max; Romanski, Joy
Abstract: In multimillennial global warming simulations with the GISS‐E2‐R climate model, we observe multicentennial shutdowns with restoration and fast overshooting in North Atlantic Deep Water production despite the absence of exogenous freshwater input. AMOC (Atlantic Meridional Overturning Circulation) cessation is associated with a sea surface salinity reduction, initiated by increases in precipitation over evaporation as the climate warms. These multicentury shutdowns are the direct result of cooling in the North Atlantic associated with an aerosol indirect effect on cloud cover. The local cooling reduces evaporation within the North Atlantic, while warming elsewhere provides moisture to maintain nearly unperturbed precipitation in this region. As global warming continues, warm temperature (low density) anomalies spread northward at depth in the North Atlantic eventually destabilizing the water column, even though precipitation input at the surface is initially unchanged. Internal ocean freshwater transports do not play an important role in initiating this behavior, as assumed by some standard metrics of AMOC stability. The importance of the aerosol indirect effect in these runs is due to its role in strengthening the sea surface temperature‐evaporation feedback; this suggests a renewed focus on surface flux observations to help assess overturning stability. The length of the AMOC reduction, and its rapid recovery, may be relevant to the onset and end of the Younger Dryas, which occurred within a warming climate during the last deglaciation. Plain Language Summary: In the Goddard Institute for Space Studies (GISS) climate model, when global warming due to higher CO2 levels was sufficiently advanced, and the effect of aerosols on cloud cover included, the North Atlantic overturning ocean circulation shuts down. It stayed off for about 1, 000 years and then suddenly resumed. Such a situation seemingly arose during the deglaciation from the last ice age. In both cases, it involved a warming planet and a relatively cooler North Atlantic ocean to begin the process and continued warming at depth in the ocean to end it. Were this to happen in the real world, it would be an additional complication for the climate system. Key Points: Global warming simulations with aerosol contributions produce NADW oscillation analogous to events during deglacial warming The North Atlantic circulation ceases and after a millennium is abruptly restored due to warming at depth Length of perturbations and rapid recovery with overshooting resemble the Younger Dryas event